Anthelmintic and Other Pharmacological Activities of the Root Bark Extracts of Albizia anthelmintica Brongn (The East and Central African Journal of Pharmaceutical Sciences, 2020)
The anthelmintic activity of water, methanol and chloroform extracts of the root bark ofAlbizia anthelmintica on strongyle-type sheep nematode eggs and larvae were examined inviiro. In addition, pharmacological tests were carried out on the water extract to confirmother ethnomedical uses of the plant. The water extract inhibited hatching of the nematodeeggs as well as development of larvae. It caused larval mortality at moderately high doses.The methanol extract had no effect on the eggs and on the development of larvae, but hadhigh activity against survival of the larvae. The chloroform extract was the least active ofthe three extracts and it had moderate effect on larval development and larval survival. Inaddition, the water extract caused contraction of the smooth muscle of the guinea pig andrabbit ileum and the rat uterus. The water extract had negative inotropic and chronotropiceffects and contractile effects on guinea pig trachea. The results support the ethnomedicaluse of this plant as an anthelmintic and for prevention of hemorrhage after birth.
Keywords: Albizia anthelmintica, anthelmintic activity, pharmacology